Work-Related Psychological Distress and Its Management: The Perspective of Employees in the Financial Industry Compared With Those in Human Services. Issue 8 (August 2019) - Vogazianos, Paris; Petkari, Eleni; Arakliti, Andri; Soteriades, Elpidoforos S.; Antoniades, Athos; Tozzi, Federica
Abstract : Objective: Investigate psychological distress and its link to stress management interventions in the financial industry (FI) in comparison to the human services (HS) sector. Method: Observational study across participating organizations in FI (66) and HS (81). Web-based version of depression anxiety stress scales (21 questions) and eight questions related to stress prevention interventions adopted by employers. Results: Indicated that FI workers are twice as likely as HS employees to present with stress and depression. Differences emerged on the availability of support at the workplace: FI workers reporting total lack of psychological support, although other forms of wellbeing promotion were more frequent. Close to 60% of individuals in the HS group reported no support (48% in the FI). Conclusion: Workers in the FI industry have increased levels of workplace stress that could be possibly attributed to absence of prevention interventions at the workplace. Abstract : Supplemental Digital Content is available in the text